Efficient Sensing of Selected Amino Acids as Biomarker by Green Phosphorene Monolayers: Smart Diagnosis of Viruses (Adv. Theory Simul. 10/2022). Issue 10 (11th October 2022) - Panigrahi, Puspamitra; Pal, Yash; Panigrahi, Akshaya; Bae, Hyeonhu; Lee, Hoonkyung; Ahuja, Rajeev; Hussain, Tanveer
Abstract : Surface Wrinkling versus Global Buckling Instabilities in Thin Film‐Substrate Systems In article 2200357, Panigrahi, Hussain and coworkers have used density functional theory simulations to explore the potential applications of green phosphorene monolayers as efficient nanobio‐sensors.